Cost Volume Profit Analysis of Small Medium Clarias sp. Hatchery Enterprise in Maguan Village, Malang Regency, East Java - Iva Dwi Wulandari; Mimit Primyastanto; Tiwi Nurjannati Utami (Faculty of Fisheries and Marine Science, Brawijaya University, 2018)
Basori Small Medium Enterprise hasn’t done financial planning yet therefore Basori Small Medium Enterprise need cost volume profit analysis. The aims of the research were to know profile, to analyze cost, sales volume, profit at